Design of Solid Geometry Learning Media to Improve Student Understanding Based On Augmented Reality - Arif Setiawan; Hanafi Bagus Panuntun (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
In the learning process at school, students have difficulty visualizing solid geometry into a real form. This study aims to develop an android-based solid geometry learning media with Augmented Reality technology and to test the feasibility of the learning media. The method used in this research is Research and Development (R&D) with the development model applying 5 stages of ADDIE namely analysis, design, development, implementation and evaluation. The results of this study are an AR learning media application that has feature namely formula and practice questions and the use of two tests, namely blackbox tests and application tests for feasibility tests. Blackbox testing and testing obtain the same results with a percentage of 100%. Thus, the application of learning media can conclude that it is very feasible to use.